Facing a Trend of Icon Simplicity: Evidence from Event-Related Potentials - Liu, Weilin; Cao, Yaqin; Liang, Xiaoning; Proctor, Robert W.; Duffy, Vincent G. (International journal of human-computer interaction, 2024)
Application icons are a pivotal part of graphical user interface of mobile devices. Despite a trend away from complexity to simplicity in user interface design, there is lack of evidence supporting the superiority of icon simplicity from a psychophysiological perspective. This study investigates the effects of icon complexity and simplicity on user cognition using an event-related potentials (ERPs) technique. Eighteen participants completed an icon cognition and evaluation experiment in an electrophysiological laboratory. Their subjective evaluations, behavioral data, and ERP data were recorded and analyzed. The results of subjective evaluation showed that the simplest icons were regarded as more useful in helping subjects extract icon information than more complex ones. For the ERP measures, P1 amplitudes induced by complex icons were larger than those elicited by simple icons. In the parietal area, P2 amplitudes and latency were larger and later for complex icons than for simple ones. Simple icons are subjectively more helpful than complex ones, partially because they demand fewer attention resources in early stimulus-driven perceptual detection of icon features (P1 during 120-190 ms) and induce more positive emotional arousal (P2 during 190-200 ms). Simple icon designs minimize cognitive demands and are deemed more helpful than complex ones. Our study highlights that the ERP technique represents a tool to explore how users process icon and interface design.